(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article provides a comprehensive analysis of psychological and social factors influencing career choice among specialized school students. The complexity of professional self-determination is examined through the interaction of internal determinants (interests, inclinations, professional identity) and external factors (family influence, social environment, economic conditions). Empirical data obtained through the “Career Choice Motivation” socio-psychological questionnaire indicate the dominant role of intrinsic motivation, alongside the significant contribution of social influences. The study also identifies gender and regional differences, highlighting the socio-cultural conditioning of career decision-making. The findings emphasize the importance of improving career guidance systems by fostering personal interests, social support, and psychological resilience in students.